2021
DOI: 10.1007/s10695-021-00989-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute hypoxia and reoxygenation on oxygen sensors, respiratory metabolism, oxidative stress, and apoptosis in hybrid yellow catfish “Huangyou-1”

Abstract: The regulation mechanism of the hybrid yellow cat sh "Huangyou-1" was assessed under conditions of hypoxia and reoxygenation by examination of oxygen sensors and by monitoring respiratory metabolism, oxidative stress, and apoptosis. The expressions of genes related to oxygen sensors (HIF-1α, HIF-2α, VHL, HIF-1β, PHD2, and FIH-1) were upregulated in the brain and liver during hypoxia, and recovered compared with control upon reoxygenation. The expressions of genes related to glycolysis (HK1, PGK1, PGAM2, PFK, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 79 publications
(93 reference statements)
0
8
0
Order By: Relevance
“…Yellow catfish (Pelteobagrus fulvidraco) is an economic important omnivorous freshwater fish species in China. It is sensitive to environmental stressors such as ammonia [26], nitrite [27], hypoxia [28], and high temperature [29]. Therefore, the aim of this study was to investigate the effects of CB on growth performance, intestinal morphology, mRNA levels of tight junction proteins and immune-related genes, and resistance to ammonia stress in juvenile yellow catfish (Pelteobagrus fulvidraco).…”
Section: Introductionmentioning
confidence: 99%
“…Yellow catfish (Pelteobagrus fulvidraco) is an economic important omnivorous freshwater fish species in China. It is sensitive to environmental stressors such as ammonia [26], nitrite [27], hypoxia [28], and high temperature [29]. Therefore, the aim of this study was to investigate the effects of CB on growth performance, intestinal morphology, mRNA levels of tight junction proteins and immune-related genes, and resistance to ammonia stress in juvenile yellow catfish (Pelteobagrus fulvidraco).…”
Section: Introductionmentioning
confidence: 99%
“…Also, the PCA showed that pgam2 was the top contributing biomarker on separating GS2 individuals from all other gill scores on PC1 ( Figure 9D ). In pufferfish ( Takifugu fasciatus ) and in hybrid yellow catfish “Huangyou-1”, higher mRNA levels of pgam2 and other glycolysis-related biomarkers were observed responding to hypoxia in the liver and brain tissues ( 78 , 79 ), posing a question to whether the gill pgam2 upregulation found in the present study points to impaired tissue oxygenation due to injury. Conversely, pgam2 was downregulated in the skin of Atlantic salmon infected with sea lice ( 80 ).…”
Section: Discussionmentioning
confidence: 55%
“…SOD has three forms, SOD1, SOD2, and SOD3, which decompose superoxide free radicals in the cytoplasm, mitochondria, and extracellular fluid, respectively, and are important antioxidant enzymes [65] . MDA, which is produced by the peroxidation of polyunsaturated fatty acids, is also an important marker of oxidative stress [ 66 , 67 ]. In this study, significant improvements were observed in antioxidant-related enzymes (e.g.…”
Section: Discussionmentioning
confidence: 99%